Religious Moderation and Hospitality in the Context of Jeremiah 29:7 - Silaban, Tri Oktavia Hartati; Sitorus, Herowati (JURNAL TERUNA BHAKTI, 2023)
A multicultural and multireligious society demands the existence of social harmony that underlies the order of life together. Therefore, it is necessary to take proactive actions to achieve inclusive togetherness among religious communities. The teaching of Jeremiah 29:7 provides instructions for taking that proactive action. The verse instructs His people to "seek the welfare of the city where they live" and "pray for the city to the LORD." In this view, religious moderation and hospitality are the keys to achieving this goal. This article is qualitative research to examine the biblical-theological ideas in Jeremiah 29:7. This study aims to strengthen the understanding of religious moderation and hospitality in the context of Jeremiah 29:7. The results of the study show that religious moderation and hospitality refer to respect for religious beliefs and the beliefs of other people without ignoring one's own religious identity. In addition, hospitality emphasizes the importance of sharing compassion and understanding when serving others.